Peak force in familial amyloidotic polyneuropathy - Tomás, Maria Teresa (2008)
Familial Amyloidotic Polyneuropathy FAP)- A neurodegenerative disease related with systemic deposition of amyloid fibers mainly at the level of the peripheral nervous system. Clinically, the disease is characterized by an autonomous sensitive-motor neuropathy, beginning nearly always in foot, and subsequently involving the hands. Purpose: Compare the levels of hand grip strength (peak force) in FAP patients with (FAPT) or without (FAPNT) liver transplant and in a healthy group (HG).